The Effect of Probiotics on Growth and Survival Rate of Fish Larvae Asian Redtail Catfish (Hemibagrus nemurus) through Pasta Feed - Winda Fatmala; Netti Aryani; Nur Asiah (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2024)
Pasta feed is one of the alternatives to replace natural food. However, the problem is that the digestibility of post larvae is still low. One approach to improve the digestibility of fish larvae of Asian redtail catfish is by giving probiotics. The research aimed to evaluate the addition of probiotics to pasta feed on fish larvae growth and survival rate in Asian redtail catfish. This research was conducted on Mei to Juni 2022 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine Faculty, Universitas Riau. The treatments in this research, namely P0 (0 mL/kg feed), P1 (10 mL/kg feed), P2 (15 mL/kg feed), P3 (20 mL/kg feed) and P4 (25 mL/kg feed). Seeds 4 days after hatching were reared in the aquarium with 15 L at stocking density 2 larvae/l for 21 days. The parameters observed were length and weight growth, specific growth rate, and survival. Feed was given 4 times/day at 40% of biomass. The result showed that the larvae fed 10 ml probiotic/kg feed had the highest growth rate (0,13 g, 1,56 cm, and 17,86 %/day), and the highest survival rate was 85,56%. The research results showed that adding probiotics in the pasta feed increased length and weight growth, specific growth rate, and survival of fish larvae Asian redtail catfish